Understanding processes of criminalisation: Insights from an Australian study of criminal law-making - McNamara, Luke (Criminology & criminal justice, 2021)
Criminalisation theory scholars have examined important questions regarding what behaviours should be criminalised and why. More recently, greater attention has been paid to linking normative accounts with empirical and historicised analyses of criminalisation practices. Building on recent work on modalities of criminalisation as a methodological tool for contextual criminalisation research, this article introduces a second analytical approach for better understanding how criminal laws are made: processes of criminalisation. We discuss the findings of a pilot study of 143 criminal law statutes enacted in three Australian jurisdictions (New South Wales, Queensland, Victoria) from 2012–2017. We conclude that a processes approach supports a nuanced appreciation of the conditions under which criminal law statutes are produced, and facilitates scrutiny of whether legislative enactments are evidence-based and a product of meaningful consultation and genuine democratic participation in law-making.